Ferrite-doped hierarchical porous biochar material with electromagnetic wave absorption performance and preparation method of ferrite-doped hierarchical porous biochar material

Through carbon dioxide activation treatment and high-temperature calcination, porous biochar material doped with CoFe2O4 magnetic nanoparticles was prepared, which solved the problem of insufficient absorption performance of biochar material and achieved strong electromagnetic wave absorption in wide bands.

CN120534969APending Publication Date: 2025-08-26CHANGCHUN UNIV OF TECH

Patent Information

Application Number
CN202510476507.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-16
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The existing biochar materials have insufficient wave absorption performance, making it difficult to form multi-stage pore structures, and it is difficult to produce ferrite through direct carbonization, resulting in a narrow absorption bandwidth and low strength.

Method used

The one-pot carbon dioxide activation treatment is adopted to convert the coconut shell into a porous carbon material doped with CoFe2O4 magnetic nanoparticles. By calcining at high temperature under the atmosphere of carbon dioxide, rich multi-stage porous structures and magnetic nanoparticles are formed, enhancing the electromagnetic wave loss performance.

Benefits of technology

By forming a rich multi-stage pore structure and CoFe2O4 magnetic nanoparticles, the scattering path and loss performance of electromagnetic waves are significantly enhanced, and the absorption performance of the material is improved, especially in a specific frequency range, which shows excellent electromagnetic wave absorption effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120534969A_ABST
    Figure CN120534969A_ABST
Patent Text Reader

Abstract

The invention provides a ferrite-doped hierarchical pore biochar material with electromagnetic wave absorption performance and a preparation method thereof, and belongs to the technical field of wave-absorbing materials. The method comprises the following steps: crushing coconut shells into powder by a wall breaking machine, cleaning the coconut shells in a potassium hydroxide solution, and then transferring the obtained coconut shells into a cobalt nitrate solution and a ferric nitrate solution for dipping and drying; and finally, transferring the coconut shells impregnated in the cobalt nitrate and ferric nitrate solution into a tubular furnace, and calcining in a carbon dioxide atmosphere to obtain the ferrite-doped hierarchical porous biochar material with the electromagnetic wave absorption performance. The material shows a richer micro-mesoporous structure and larger pore volume and specific surface area compared with other activation methods under calcination activation of metals such as iron and cobalt in a carbon dioxide atmosphere, the micropore volume reaches 0.725 cm < 3 >. G <-1 >, and the mesopore volume reaches 0.695 cm < 3 >. G <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of wave-absorbing materials, and in particular relates to a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance and a preparation method thereof. Background Art

[0002] Carbon materials, such as carbon fibers, carbon nanotubes, graphene, and biocarbon materials, have been widely used in the field of EMWAE (Electromagnetic wave absorption) due to their excellent dielectric properties. Biocarbon materials can achieve this enhanced EWM loss due to their numerous heteroatom-doped materials. Their unique porous structure provides excellent electromagnetic wave dissipation. Furthermore, biocarbon's simple preparation process, eco-friendliness, low cost, and widespread availability make it an excellent choice for EMWA materials.

[0003] Currently, biomass waste rice husks are used as raw materials to synthesize corrugated biomass hierarchical porous carbon (BHPC) materials through carbonization and alkali activation processes to enhance the performance of EWMA (Advanced Sustainable System, 2022, 6, 2100454.) Or a simple carbonization method is used to prepare kapok microtubes. Their hollow tube structure gives the composite material excellent microwave absorption performance (Journal of Physics D: Applied Physics, 50 (2017), 135303.). However, single biomass carbon materials often have disadvantages such as narrow absorption bandwidth and low absorption intensity due to their single dielectric loss properties. To date, biochar materials with magnetic metal doping, such as ferrite-doped or alloy-doped biochar, have become the main method to solve the insufficient microwave absorption performance of single biochar materials.

[0004] Magnetic materials, such as metal elements, alloys, metal oxides, and ferrites (Chinese Patent CN202210924419.0), centered around Fe / Co / Ni, exhibit significant advantages in electromagnetic wave absorption. Therefore, doping biochar with magnetic materials can effectively enhance the biochar's magnetic loss performance. It can also create more heterogeneous interfaces in the biomass carbon, causing interfacial polarization and enhancing dielectric loss, thereby improving EMWA performance.

[0005] According to the Maxwell-Garnett theory, the dielectric constant of air is much smaller than that of carbon materials. Porous, hollow, core-shell, layered, and flower-shaped structures cause electromagnetic waves to reflect multiple times on the surface of the absorbing material, greatly extending the transmission path of the electromagnetic waves. Therefore, making the carbon material porous can significantly reduce its dielectric constant, thereby optimizing impedance matching and improving EMW absorption performance (Chinese Patent CN201611115882.1). However, current carbonization methods are difficult to directly produce multi-level pore structures, and direct high-temperature carbonization methods are difficult to form metal oxides. Summary of the Invention

[0006] The purpose of the present invention is to solve the problems of insufficient absorption performance of single biochar materials, difficulty in forming ferrite by direct carbonization method, and difficulty in obtaining rich multi-level pore structures (mesopores, micropores) through simple processes, thereby providing a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance and a preparation method thereof. The method converts coconut shells loaded with iron and cobalt metals into porous carbon absorbing materials doped with CoFe2O4 magnetic nanoparticles in one step through a simple one-pot activation treatment with carbon dioxide.

[0007] To achieve the above object, the present invention is implemented through the following technical solutions:

[0008] The present invention discloses a method for preparing a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance, comprising the following steps:

[0009] Step 1: Crush the coconut shell into powder using a wall-breaking machine, wash it in a potassium hydroxide solution, then clean the coconut shell washed with potassium hydroxide solution using deionized water ultrasonic vibration and dry it;

[0010] Step 2: Transfer the coconut shell obtained in step 1 to a cobalt nitrate solution and an iron nitrate solution and immerse and dry;

[0011] Step 3: The coconut shells soaked in the cobalt nitrate and ferric nitrate solution obtained in step 2 are transferred to a tubular furnace and calcined under a carbon dioxide atmosphere to obtain a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance.

[0012] Preferably, the concentration of the potassium hydroxide solution in step 1 is 1 mol / L, and the coconut shell is washed in the potassium hydroxide solution for 4 hours.

[0013] Preferably, the drying temperature in step 1 is 50-80° C., and the drying time is 20-24 hours.

[0014] Preferably, the concentration of the cobalt nitrate solution in step 2 is 0.25 mol / L-0.75 mol / L, the concentration of the ferric nitrate solution is 0.5 mol / L-1.5 mol / L, and the immersion time is 48 h-60 h.

[0015] Preferably, the drying temperature in step 2 is 50-80° C., and the drying time is 20-24 hours.

[0016] Preferably, the carbon dioxide flow rate in step 3 is 0.3 L / min-0.4 L / min.

[0017] Preferably, the calcination temperature in step 3 is 600° C.-1050° C., the heating rate is 10° C. / min, the calcination time is 30 min, and then the temperature is lowered to room temperature.

[0018] The present invention also provides a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance obtained by the above preparation method.

[0019] Beneficial effects of the present invention

[0020] The present invention provides a method for preparing a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption properties. The method comprises crushing coconut shells into powder using a wall-breaking machine, washing them in a potassium hydroxide solution, drying them after removing impurities and oil, transferring the resulting coconut shells to a solution of cobalt nitrate and ferric nitrate for immersion, allowing FeO and CoO to enter the pores of the coconut shells, drying them, and finally calcining them at high temperature in a CO2 atmosphere. The present invention activates the material through high-temperature calcination in a CO2 atmosphere, oxidizing FeO to Fe3O4, which then reacts with CoO to form CoFe2O4 magnetic nanoparticles, enhancing electromagnetic wave loss performance. Furthermore, with CO2 and Co and Fe components acting as physical and chemical activators, respectively, the coconut shells effectively form a large number of micro- and mesoporous structures during the carbonization process, extending the scattering path of electromagnetic waves and thus improving the product's absorption performance.

[0021] Compared to existing technologies, the present invention achieves a rich multi-level porous structure and CoFe2O4 magnetic nanoparticles through a simple process. CO2, Co, and Fe act as physical and chemical activators, respectively, on the carbon matrix to form a rich multi-level porous structure. Activation under a CO2 atmosphere effectively forms a large number of microporous structures during the coconut shell carbonization process, while the metal promotes the formation of mesopores during the activation process. The synergistic effect between CO2 and the CoFe components further deepens the activation process, creating a richer pore structure. During the CO2 activation process, FeO is oxidized to Fe3O4, which then reacts with CoO to form CoFe2O4 magnetic nanoparticles.

[0022] The formation of a multi-level pore structure enriches the pore structure of the biochar surface and obtains a larger pore volume, which causes multiple reflections, scattering and dissipation of electromagnetic waves while extending the scattering path of electromagnetic waves. The formation of CoFe2O4 magnetic nanoparticles causes the product to cause strong magnetic loss through natural resonance, eddy current effect, and exchange resonance, greatly enhancing the electromagnetic wave loss performance. Biomass carbon with a multi-level pore structure loaded with CoFe2O4 magnetic nanoparticles is calcined at high temperature in a tubular furnace under a CO2 atmosphere, thereby preparing a ferrite-doped multi-level pore biochar material with electromagnetic wave absorption performance. This material exhibits a richer micro-mesoporous structure, a larger pore volume and specific surface area compared to other activation methods under the calcination activation in a carbon dioxide atmosphere with metals such as iron and cobalt, and the micropore volume reaches 0.725cm 3 .g -1 , the mesopore volume reaches 0.695 cm 3 .g -1 , this method provides broad prospects for the design of high-efficiency absorbing materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD spectra of sample YKCC-1, sample YKCC-2, and comparative sample YKNC prepared in Examples 1-2 and Comparative Example 1 of the present invention.

[0024] Figure 2 SEM images of sample YKCC-1 (a), sample YKCC-2 (b), and comparative sample YKNC (c) prepared in Examples 1-2 and Comparative Example 1 of the present invention.

[0025] Figure 3 The real part of magnetic permeability (a), the imaginary part of magnetic permeability (b) and the tangent value of magnetic permeability (c) of YKCC-2 prepared in Example 2 of the present invention.

[0026] Figure 4 The three-dimensional RL value (a), three-dimensional RL value contour map (b) and two-dimensional RL curve (c) of sample YKCC-2 prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0028] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any intermediate value within a stated value or stated range and any other stated value or intermediate value within the stated range is also encompassed by the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.

[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.

[0030] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the present invention. The present description and examples are intended to be illustrative only.

[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0032] The present invention discloses a method for preparing a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance, comprising the following steps:

[0033] Step 1: crush the coconut shell into powder by a wall breaking machine, put it into potassium hydroxide solution for cleaning, the concentration of the potassium hydroxide solution is preferably 1 mol / L, and the cleaning time is preferably 4 hours to remove impurities and oil stains, and then the coconut shell washed with potassium hydroxide solution is ultrasonically cleaned with deionized water to remove potassium hydroxide residual on the surface, and dried, the drying temperature is preferably 50-80°C, and the drying time is preferably 20-24 hours; the coconut shells are all mature, dry biomass coconut shells.

[0034] Step 2: Transferring the coconut shell obtained in step 1 to a cobalt nitrate solution and a ferric nitrate solution and immersing and drying; the concentration of the cobalt nitrate solution is preferably 0.25 mol / L-0.75 mol / L, more preferably 0.25 mol / L-0.5 mol / L, the concentration of the ferric nitrate solution is preferably 0.5 mol / L-1.5 mol / L, more preferably 0.5 mol / L-1.0 mol / L, the immersion time is preferably 48 h-60 h, the drying temperature is preferably 50-80 ° C, and the drying time is preferably 20-24 h;

[0035] Step 3: The coconut shell soaked in the cobalt nitrate and ferric nitrate solution obtained in step 2 is transferred to a tubular furnace and calcined under a carbon dioxide atmosphere. The carbon dioxide flow rate is preferably 0.3L / min-0.4L / min, the calcination temperature is preferably 600°C-1050°C, more preferably 900°C, the heating rate is preferably 10°C / min, the calcination time is preferably 30min, and then cooled to room temperature to obtain a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance.

[0036] According to the present invention, the detergents and impregnation solutions used in all steps, such as potassium hydroxide solution, cobalt nitrate solution, ferric nitrate solution, etc., use deionized water as solvent.

[0037] The present invention also provides a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption properties obtained by the above-mentioned preparation method. This material exhibits a richer micro-mesoporous structure, as well as a larger pore volume and specific surface area compared to other activation methods, when calcined and activated in a carbon dioxide atmosphere with metals such as iron and cobalt. The micropore volume reaches 0.725 cm 3 .g -1 , the mesopore volume reaches 0.695 cm 3 .g -1 , and finally form the multi-level porous biochar material loaded with CoFe2O4 nanoparticles described in the present invention.

[0038] Unless otherwise specified, all raw materials and instruments used in the following examples of the present invention are commercially available.

[0039] Example 1

[0040] This embodiment provides a method for preparing a ferrite-doped multi-level porous biochar material with excellent electromagnetic wave absorption performance, which comprises the following steps:

[0041] (1) 3 g of coconut shells were crushed into powder using a wall crusher and soaked in a 1 mol / L potassium hydroxide solution for 4 h to remove impurities and oil. The coconut shells were then ultrasonically cleaned with deionized water to remove residual potassium hydroxide on the surface. The washed coconut shells were placed in an 80 °C oven and dried overnight.

[0042] (2) The coconut shell obtained from step (1) was transferred to a 0.25 mol / L cobalt nitrate and 0.5 mol / L ferric nitrate solution and immersed for 48 h. After the immersion, the coconut shell was placed in an 80° C. oven and dried overnight.

[0043] (3) The sample obtained in step (2) was placed in a high-temperature resistant ceramic tray and moved into a tube furnace for high-temperature carbonization activation at 900°C for 30 min under a CO2 atmosphere, where the CO2 gas flow rate was fixed at 0.4 L / min and the heating rate was 10°C / min. The obtained sample was named YKCC-1.

[0044] Example 2

[0045] This embodiment provides a method for preparing a ferrite-doped multi-level porous biochar material with excellent electromagnetic wave absorption performance, which comprises the following steps:

[0046] (1) 3 g of coconut shells were crushed into powder using a wall crusher and soaked in a 1 mol / L potassium hydroxide solution for 4 h to remove impurities and oil. The coconut shells were then ultrasonically cleaned with deionized water to remove residual potassium hydroxide on the surface. The washed coconut shells were placed in an 80 °C oven and dried overnight.

[0047] (2) The coconut shell obtained from step (1) was transferred to a 0.5 mol / L cobalt nitrate and 1 mol / L ferric nitrate solution and immersed for 48 h. After the immersion was completed, the coconut shell was placed in an 80° C. oven and dried overnight.

[0048] (3) The sample obtained in step (2) was placed in a high-temperature resistant ceramic tray and moved into a tube furnace for high-temperature carbonization activation at 900°C for 30 min under a CO2 atmosphere, where the CO2 gas flow rate was fixed at 0.4 L / min and the heating rate was 10°C / min. The obtained sample was named YKCC-2.

[0049] Comparative Example 1

[0050] This comparative example provides a method for preparing a ferrite-doped multi-level porous biochar material, which comprises the following steps:

[0051] (1) 3 g of coconut shells were crushed into powder using a wall crusher and soaked in a 1 mol / L potassium hydroxide solution for 4 h to remove impurities and oil. The coconut shells were then ultrasonically cleaned with deionized water to remove residual potassium hydroxide on the surface. The washed coconut shells were placed in an 80 °C oven and dried overnight.

[0052] (2) The coconut shell fraction obtained from step (1) was transferred to a 0.5 mol / L cobalt nitrate and 1 mol / L ferric nitrate solution and immersed for 48 h. After the immersion, the coconut shell fraction was placed in an 80° C. oven and dried overnight.

[0053] (3) The sample obtained in step (2) was placed in a high-temperature resistant ceramic tray and moved into a tube furnace for high-temperature carbonization activation at 900°C for 30 min under a N2 atmosphere, where the N2 gas flow rate was fixed at 0.4 L / min and the heating rate was 10°C / min. The obtained sample was named YKCN.

[0054] The porous biochar materials obtained in each experimental example and comparative example were subjected to X-ray diffraction test and high-resolution electron microscope photography. The results are shown in Figure 1 , Figure 2 .

[0055] The X-ray diffraction (XRD) of the sample is as follows Figure 1 As shown, Example 2 and Example 1 have obvious diffraction peaks near 2θ=18.4° to 74.1°, which are respectively attributed to the (003), (012), (104), (113), (006), (024), (205), (116) and (315) crystal planes of CoFe2O4; the peaks near 2θ=44.7° and 65.1° in Comparative Example 1 represent the (110) and (002) crystal planes of Co3Fe7.

[0056] Figure 2 (a), (b), and (c) correspond to Example 1, Example 2, and Comparative Example 1, respectively.

[0057] In Examples 1 and 2, the metal impregnated in the biochar was activated under a CO2 atmosphere to form CoFe2O4 magnetic nanoparticles due to the combined effects of CO2 activation on the carbon matrix and the high-temperature redox reaction between the metal component and the biochar. The combined effects of CO2 and the CoFe2O4 magnetic nanoparticles resulted in a multi-level porous structure in the biochar. The increased metal content also contributed to an increase in the specific surface area and pore volume of the material, resulting in uneven surface roughness in Examples 1 and 2. The degree of roughness in Example 2 was greater than in Example 1. Although the surface of Comparative Example 1 also exhibited uneven surface roughness, the degree of roughness was less than that in Examples 1 and 2. This is due to the nitrogen protection of the carbon matrix and the high-temperature redox reaction between the metal component and the biochar in Comparative Example 1, which resulted in the metal impregnated in the biochar being reduced to a metal alloy by the biochar under the N2 atmosphere. This alloy then formed a small amount of porous structure in the biochar. The porous biochar materials obtained from each experimental example and comparative example were subjected to nitrogen adsorption and desorption testing. The results are shown in Table 1.

[0058] Table 1 Pore structure properties of carbon materials

[0059]

[0060] As shown in Table 1, the biochar materials obtained in the tests had varying specific surface areas. Comparative Example 1, prepared under an N2 atmosphere, exhibited fewer defects, resulting in a lower porosity than Example 2. The increased metal content in Examples 1 and 2 shifted the porosity toward the higher metal content.

[0061] The magnetic parameters of the porous biochar materials obtained in each embodiment and comparative example were tested, and the results are shown in Table 2.

[0062] Table 2 Magnetic parameters

[0063]

[0064] Comparative Example 1, containing a highly magnetic Fe and Co metal alloy, exhibits a higher saturation magnetization (Ms) and lower coercivity. The lower content of CoFe2O4 magnetic nanoparticles in Example 1 results in the highest Hc, but also a lower Ms value. In Example 2, increasing the metal impregnation level and the CoFe2O4 magnetic nanoparticle content slightly decreases Hc, but significantly improves Ms, achieving a favorable trade-off between Hc and Ms.

[0065] The real part (μ′) and imaginary part (μ″) of the magnetic permeability, the real part (ε′) and imaginary part (ε″) of the complex dielectric constant of the ferrite-doped multi-level porous biochar material with excellent electromagnetic wave absorption performance in Example 2 were tested, and the three-dimensional RL value and the three-dimensional RL value contour map were drawn.

[0066] Figure 3 The values ​​of the real part (μ′) and imaginary part (μ″) of the magnetic permeability of the biochar composite material are shown. Because relaxation occurs during the magnetization process of Example 2, the μ′ and μ″ value curves in the frequency range of 2-18 GHz show strong oscillation peaks. The three-dimensional RL value, three-dimensional RL value contour map and two-dimensional RL curve of the ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance described in Example 2 are shown in FIG. Figure 4 shown. Figure 4 The EAB values ​​of Example 2 at different thicknesses show strong absorption peaks. At a thickness of 3.8 mm and a frequency of 6.46 GHz, the RLmin value is -38.1 dB, and the EAB value reaches 2 GHz (5.6-7.6 GHz). At a thickness of 4.2 mm, the EAB value reaches 2.8 GHz (5.2-8 GHz).

[0067] In the present invention, the principles and implementations of the present invention are illustrated by specific examples. The description of the above embodiments is only intended to help understand the method and core concept of the present invention. At the same time, based on the concept of the present invention, those skilled in the art will appreciate that there may be some variations in the specific implementation and scope of application. In short, the contents of this specification should not be construed as limiting the present invention.

Claims

1. A method for preparing a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance, characterized in that: The following steps are involved: Step 1: Crush the coconut shell into powder using a wall-breaking machine, wash it in potassium hydroxide solution, then clean the coconut shell washed with potassium hydroxide solution with deionized water and ultrasonically shake it, and dry it; Step 2: Transfer the coconut shell obtained in step 1 to a cobalt nitrate solution and an iron nitrate solution and immerse and dry; Step 3: The coconut shells soaked in the cobalt nitrate and ferric nitrate solution obtained in step 2 are transferred to a tubular furnace and calcined under a carbon dioxide atmosphere to obtain a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance.

2. The method for preparing a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance according to claim 1, characterized in that: The concentration of the potassium hydroxide solution in step 1 is 1 mol / L, and the coconut shell is washed in the potassium hydroxide solution for 4 hours.

3. The method for preparing a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance according to claim 1, characterized in that: The drying temperature in step 1 is 50-80° C., and the drying time is 20-24 hours.

4. The method for preparing a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance according to claim 1, characterized in that: The concentration of the cobalt nitrate solution in step 2 is 0.25 mol / L-0.75 mol / L, the concentration of the ferric nitrate solution is 0.5 mol / L-1.5 mol / L, and the immersion time is 48 h-60 h.

5. The method for preparing a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance according to claim 1, characterized in that: The drying temperature in step 2 is 50-80° C., and the drying time is 20-24 hours.

6. The method for preparing a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance according to claim 1, characterized in that: The carbon dioxide flow rate in step 3 is 0.3 L / min-0.4 L / min.

7. The method for preparing a ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance according to claim 1, characterized in that: The calcination temperature in step 3 is 600° C.-1050° C., the heating rate is 10° C. / min, the calcination time is 30 min, and then the temperature is lowered to room temperature.

8. Ferrite-doped multi-level porous biochar material with electromagnetic wave absorption performance obtained by the preparation method according to claim 1.

Citation Information

Patent Citations

  • Broadband electromagnetic wave absorbing material based on polyaniline graphene three-dimensional porous structure

    CN107072128A

  • Soft magnetic ferrite wave-absorbing material, preparation method thereof and composite wave-absorbing material

    CN115084870A

Cited By

  • Lotus leaf carbon-based iron-cobalt composite hollow broadband wave-absorbing material as well as preparation method and application thereof

    CN120790928A